2014
DOI: 10.1016/j.apal.2014.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Selective covering properties of product spaces

Abstract: We study the preservation of selective covering properties, including classic ones introduced by Menger, Hurewicz, Rothberger, Gerlits and Nagy, and others, under products with some major families of concentrated sets of reals. Our methods include the projection method introduced by the authors in an earlier work, as well as several new methods. Some special consequences of our main results are (definitions provided in the paper): \be \item Every product of a concentrated space with a Hurewicz $\sone(\Ga,\… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…1 and 1.2] proved the same result using weaker hypotheses). It was later shown that, in the realm of hereditarily Lindelöf spaces, every productively Lindelöf space is productively Hurewicz and productively Menger [16,Theorem 8.2]. In our previous paper, we proved that in that realm, every productively Menger space is productively Hurewicz [19,Theorem 4.8].…”
Section: General Semifiltersmentioning
confidence: 80%
See 2 more Smart Citations
“…1 and 1.2] proved the same result using weaker hypotheses). It was later shown that, in the realm of hereditarily Lindelöf spaces, every productively Lindelöf space is productively Hurewicz and productively Menger [16,Theorem 8.2]. In our previous paper, we proved that in that realm, every productively Menger space is productively Hurewicz [19,Theorem 4.8].…”
Section: General Semifiltersmentioning
confidence: 80%
“…(And if not, does (Hurewicz, Lindelöf ) × ⊆ Hurewicz × ? A scale is a ≤ * -increasing sequence { s α : α < d } ⊆ [N] ∞ that is ≤ ∞ -unbounded in [N] ∞ .If S is a scale then, in the realm of hereditarily Lindelöf spaces, the real space S ∪ [N] <∞ is productively Hurewicz and productively Menger[16, Theorem 6.2]. A positive solution of the following problem implies the same assertion for general spaces.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…As the following fact established in [21] shows, the inequality u < g imposes strong restrictions on the structure of Menger spaces. Lemma 2.3.…”
Section: Lemma 21mentioning
confidence: 98%
“…A space X is called productively P if X × Y has the property P for each space Y satisfying P . Productively P properties have been studied by many authors (see, e.g., [3,27,34]). …”
Section: Comments On Productivitymentioning
confidence: 99%